Islam Nusantara dan Diskursus Politik: Analisis Wacana Kritis Berita di CNN Indonesia - Mahmud Hibatul Wafi; Saipudin Ikhwan; Tito Handoko (Jurnal Komunikasi Islam, 2022)
This paper reports on textual analysis research of three news media stories published by CNN Indonesia (cnninodenesia.com) in 2019 pertaining to Islam Nusantara and politics, using a critical discourse analysis approach proposed by Teun A. Van Dijk. Findings reveal that in the political context of Islam Nusantara (Islam of the Archipelago) discourse offers solutions to prevent conflict, tragedy, and violence in the name of religion. Further, it is also found that the political situation in Indonesia, which was rife with religious issues and increased intolerance, made Islam Nusantara dragged into the political sphere. This is because Partai Kebangkitan Bangsa (The National Awakening Party/PKB) which was historically born from the womb of the Nahdlatul Ulama was one of the ruling coalition parties.